Algorithm for selecting the winning strategies in the processes of managing the state of the system "supplier – consumer" in the presence of aggressive competitor - Domina, Olena; Lunin, Dmitry; Barabash, Olga; Balynska, Olga; Paida, Yurii; Mikhailova, Liudmyla; Niskhodovska, Olena (Eastern-European Journal of Enterprise Technologies, 2018)
The issue examined in this work relates to the search for an optimal pricing strategy by an enterprise-supplier in case it faces a new competitor that offers products at a lower price. The emergence of such a problem necessitates looking for a rational way to reduce its selling price, in order to prevent losing in an aggressive competitive environment, formed by new players entering the market with proposals that are obviously better. To resolve this problem, we have developed an algorithm for selecting the winning strategies based on the estimation of strategic capabilities of a competitor under conditions of uncertainty. It has been proposed, in order to assess the cost of a product in the system "supplier-consumer", to apply the concept of the l- level scale. It is shown that, given such a representation, it becomes possible to employ a dimensionless estimation of product pricing, regardless of its type or natural cash value. For a formalized description of relations between an enterprise- supplier and a competing company, it is proposed to use the theory of strategic games, in which a game matrix is built based on universal regression equations. A feature of the proposed solutions is that the value of winning in the game matrix is defined by solving an optimization problem based on the regression equation that describes the impact of transportation costs, profit, and a value-added tax (VAT) on the price of the game. It has been established that, given such a description, the game that is played has a saddle point with the net price of the game z=–0.5. Based on mathematical modelling, it was established that the selection of a supplier company is limited by strategies at which own profit must be close to the average or the minimally possible value. We have constructed a predictive model for strategic opportunities of a competitor in the system "supplier-consumer", representing a universal regression equation. Based on it, an adjustment of numerical indicators for the components in product pricing can be made. It is shown that such an adjustment allows the existence of multiple alternatives, neutralizing competitor's advantages. We have substantiated constraints for the solutions derived, related to two factors: an assumption about the accuracy of determining the pricing components of a competitor, and the presence of taxation specificity in international cargo transportation.